Organ-protective antidiabetic prescriptions in type 2 diabetes – a single institution experience - Mira Siderova; Georgi Shopov; Gabriela Kehayova; Stela Dragomanova (Pharmacia)
The aim of this study was to evaluate the antidiabetic therapy during hospitalization, as well as that recommended at discharge from a single university endocrinology clinic for all type 2 diabetes patients admitted over a 12-month period. Of the 464 cases, 345 (74.4%) were emergency admissions and 119 (25.6%) were planned hospitalizations for poor glycemic control. At discharge, one antidiabetic medication was prescribed in 133 patients (28.7%), two in 169 (36.3%), three in 103 (22.2%), and 48 (10.4%) received four or more glucose-lowering agents. Of all patients, 175 (37.7%) were taking sodium-glucose cotransporter 2 inhibitors (SGLT2i), 71 (15.3%) glucagon-like peptide 1 receptor agonists (GLP1-RAs), and 42 (9.1%) both organ-protective classes. Among patients with concomitant cardiovascular disease, chronic kidney disease, or both (n = 300; 64.7%), SGLT2i was prescribed in 150 (50.0%), GLP1-RA in 51 (17.0%), and both in 34 individuals (11.3%). Our results indicate that more than half of the patients at cardio-renal risk (55.7%) received at least one organ-protective medication.